1612 Combinatorial glycoarray detects diverse new antibody specificities in Guillain-BarrÉ syndrome. Issue 3 (9th February 2012) - Rinaldi, S; Brennan, K M; Kalna, G; Walgaard, C; Jacobs, B C; Yu, R K; Willison, H J
Abstract : Auto-antibodies are often detected in Miller-Fisher and axonal Guillain-Barré syndromes (MFS/GBS), yet are rarely found in the more common demyelinating subtype (AIDP). The description of ganglioside complex (GSC) antibodies has raised the possibility that potential antigenic targets have previously been overlooked. We used a glycoarray to screen sera from 181 GBS patients and 74 controls against 162 lipid complexes. IgG antibodies in 113 GBS patients (62.4%) vs 11 controls (14.9%) showed binding to one or more antigens on the array (p<0.001). Of confirmed AIDP cases, 62.4% were also positive using the array, compared with only 10.6% by routine ELISA. The most intense binding signals were generated by antibodies binding GSCs. When disease associated sera were positive for binding to one or more single glycolipids, they often bound to complexes consisting of two separate glycolipids, neither of which they bound singly (complex enhanced binding). When control sera bound single lipid antigens such as sulfatide, they were unable to bind sulfatide complexes (complex attenuated binding). Analysis of intensity values revealed 9 antigens with statistically increased binding in GBS as compared with controls. The presence of certain antibodies correlated with disease severity and the requirement for mechanical ventilation. The combinatorial glycoarray technique has substantially increased the number of glycolipid antibody specificities significantly associated with GBS. The next step will be to generate monoclonal antibodies complex binding patterns and investigate their pathogenic effects.